Comparative Analysis of Sustainability of Driyarkara College of Philosophy and Widya Sasana College of Philosophy According To ISO 26000 Perspective - Rafael Mathando Hinganaday; Maria R. Nindita Radyati; Maria Ariesta Utha (Green Publisher Indonesia, 2023)
Philosophy can help giving an ethical foundation for promoting sustainability of nature and respect for humanity in management and business practices. In this case, schools of philosophy need to take a role in promoting philosophy related to the theme of sustainability. This research aims to analyze the sustainability of schools of philosophy by taking Sekolah Tinggi Filosofi Driyarkara and Sekolah Tinggi Filosofi Widya Sasana as objects. The research is conducted according to the perspective of ISO 26000 and using in-depth interview as the method for collecting data from 62 respondents. The variables of research are the strategies of sustaining inclusivity, competitive advantage (Sustainable Value Proposition), integration of SDGs and the concept of social responsibility within curriculum, governance according to ISO 26000, and the relation between curriculum and SDGs no. 4, 5, and 16. Findings show that both institutions still need to adjust their curricula and governances according to ISO 26000.